2017
DOI: 10.1111/epi.13905
|View full text |Cite
|
Sign up to set email alerts
|

Methodological standards and functional correlates of depth in vivo electrophysiological recordings in control rodents. A TASK1‐WG3 report of the AES/ILAE Translational Task Force of the ILAE

Abstract: Summary This paper is a result of work of Translational Task Force of the ILAE Neurobiology Commission. The aim is to provide acceptable standards and interpretation of results of electrophysiological recordings in vivo in control rodents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Flexible multielectrode arrays can also be used for recording epidurally from the brain's surface . Depth electrodes will be the focus of a different article in this Supplement …”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flexible multielectrode arrays can also be used for recording epidurally from the brain's surface . Depth electrodes will be the focus of a different article in this Supplement …”
Section: Methodological Considerationsmentioning
confidence: 99%
“…18 Depth electrodes will be the focus of a different article in this Supplement. 19 The limitations of skull-attached recordings in rodents include the short interelectrode distances due to anatomical spatial constraints and the volume conduction (see Data S1). 20 Selection of electrode derivations that are farther apart can aid in the identification of the source localization of particular EEG rhythms/seizure initiation zones.…”
Section: Types Of Eeg Recordings and Electrodesmentioning
confidence: 99%
“…This manuscript of the ILAE/AES Joint Translational TF introduces the preclinical CDEs organized into case report forms (CRFs) for preclinical studies utilizing electroencephalography (EEG), video‐EEG (vEEG), or electrophysiologic recordings in rodents. The recently published reports of the TASK1 groups of ILAE/AES Joint Translational TF outline some of the methodologic and reporting practices for the acquisition, interpretation, and analysis, including software‐based, of EEG performed in experimental control rodents . In addition, readers may refer to additional considerations on reporting experimental methods and welfare of animals used for epilepsy research reported by Lidster et al.…”
mentioning
confidence: 99%
“…The recently published reports of the TASK1 groups of ILAE/AES Joint Translational TF outline some of the methodologic and reporting practices for the acquisition, interpretation, and analysis, including software-based, of EEG performed in experimental control rodents. [9][10][11][12] In addition, readers may refer to additional considerations on reporting experimental methods and welfare of animals used for epilepsy research reported by Lidster et al (2016). 13 Here, we discuss how some of these principles can be incorporated in CDE and CRF documents to help guide the reader about which data and metadata would be helpful to be reported and catalogued in such forms.…”
mentioning
confidence: 99%
“…The TASK1‐WG1 group reports on best practices pertaining to studies using surface or epi‐/subdural EEG in adult rodent controls . The TASK1‐WG3 group addresses the methodologies and interpretation of depth electrophysiologic in studies in vivo in adult rodent controls, whereas the TASK1‐WG4 group focuses on in vitro electrophysiologic studies . The TASK1‐WG5 group proposes standards for data acquisition and analysis for the electrophysiologic recordings .…”
mentioning
confidence: 99%